Estimation of Fasting Blood Glucose and Lipid Profile among Patients with Psychotics Disorders under Medications - Abdrabo, AbdElkarim A.; Sheek, Shaimaa M. (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 2 (2019), 2019)
Background : Individuals who are treated with antipsychotic medications especially atypical group are facing several metabolic and biochemical changes that might put them at higher risk of developing several diseases. The aim of this study was to evaluate the fasting blood glucose level and lipid profile among those with common psychotic disorders under effect of atypical antipsychotic drugs compared with healthy population. Materials and Methods: A laboratory- based case control study was conducted and carried out in Khartoum State (AlTigani AlMahy Hospital for Psychotic and Mental Diseases) from May to November 2017. The samples were drawn from fifty patients of common psychotic disorders as case group and another fifty from healthy individuals as control group to estimate the level of fasting blood glucose and lipid profile using Mindary Biosystems PS200. Results: out of 50 cases, 52% were males and 48% females. It was found that there was a significant increase in mean of all tested parameters, fasting blood glucose (FBG) (109.19±26.27), Total Cholesterol (167.23±41.79), Triglyceride (161.80±59.29) and Low Density Lipoprotein (LDL) (66.42±16.72) but decrease in High Density Lipoprotein (HDL) (53.96±17.86), all with (p.value 0.00) compared to control. There was no correlation between parameters and age, but positive correlation was observed between LDL and duration (R-0.047).  Conclusion: Individuals under atypical antipsychotic medications had higher levels of fasting blood glucose and lipid profile than normal individuals.